2021
DOI: 10.1177/15266028211049339
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Drug-Eluted Stenting (Zilver PTX) in Patients With Femoropopliteal Occlusive Disease a Single Center Experience

Abstract: Background: Few industry sponsored trials reported satisfactory outcomes in the use of drug-eluting stents (DES) for treatment of femoropopliteal arterial disease. This study analyzed the early/late clinical outcome from a real world single center. Patient Populations/Methods: A total of 115 limbs treated with Zilver PTX were analyzed for: major adverse limb event (MALE: above ankle limb amputation/major intervention at 1 year), major adverse events (MAEs; death, amputation, and target lesion thrombosis/reinte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Studies have shown that about 50% of Chinese patients are insensitive to platinum-based chemotherapy drugs and 5-Fu due to secondary multidrug resistance. Another unavoidable problem is that chemotherapy drugs cause severe collateral damage to actively proliferating normal cells [ 11 , 12 ]. Therefore, it is of great significance to find a highly targeted and noncytotoxic drug for postoperative chemotherapy and nonsurgical treatment of SC [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that about 50% of Chinese patients are insensitive to platinum-based chemotherapy drugs and 5-Fu due to secondary multidrug resistance. Another unavoidable problem is that chemotherapy drugs cause severe collateral damage to actively proliferating normal cells [ 11 , 12 ]. Therefore, it is of great significance to find a highly targeted and noncytotoxic drug for postoperative chemotherapy and nonsurgical treatment of SC [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is not fully in line with results in studies of nitinol stenting in the FP region. 16,17,[20][21][22][23][24][25][26][27]29,32,34,48,53,54 A possible reason for low primary patency is a high percentage of total occlusions, long lesions with overall median length of 240 (163-285) mm, and overall Rutherford class 5 (4-5), indicating a high incidence of complex lesions and subjects in our study population.…”
Section: Discussionmentioning
confidence: 88%
“…However, some other publications on BMS and DES report on a similar limited number of participants. 16,34,37,53,67 Another limitation is the relative high rate of technical failure in the trial. The TS rate was unusually suboptimal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations